2008
DOI: 10.1080/15348430802143378
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining a Dual Language Immersion Program: Features of Success

Abstract: The promise of dual language education has spurred a movement in the field of bilingual education to shift from remedial programs to enrichment forms of bilingual education. Although research supports the effectiveness of such programs, many programs do not maintain their level of implementation and quickly revert to their original remedial form. This research looks at one elementary campus that has implemented a 2-way dual language program for more than a decade. Findings indicate that pedagogical equity, qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 19 publications
(16 reference statements)
1
79
0
Order By: Relevance
“…Staffing is counted as one of the important factors in various studies (Alanis and Rodriguez 2008;Senesac 2002). It is challenging to employ and/or retain good bilingual teachers (Day and Shapson 1996).…”
Section: Downloaded By [Mcmaster University] At 19:15 20 December 2014mentioning
confidence: 99%
“…Staffing is counted as one of the important factors in various studies (Alanis and Rodriguez 2008;Senesac 2002). It is challenging to employ and/or retain good bilingual teachers (Day and Shapson 1996).…”
Section: Downloaded By [Mcmaster University] At 19:15 20 December 2014mentioning
confidence: 99%
“…Principals' knowledge and perceptions of how programs should be implemented is also important when implementing programs for ELLs because negative attitudes, prejudices, and misinformation about bilingual education/second language programs may lead to inappropriate practices (Alanis & Rodriguez, 2008;Lindholm-Leary, 2001;Rodriguez, 2009). Considering the key role that principals play in the successful implementation of programs for ELLs and their potential impact on students' academic success and teacher retention, it is important to investigate principals' knowledge and perceptions of the second language programs that are being implemented in their schools.…”
Section: Introductionmentioning
confidence: 99%
“…There are strong proponents of the dual language method (Alanís & Rodriguez, 2008;Genesee et al, 2005) as well as the English only method (Echevarria, Short, & Powers, 2006;Rossell, 2005). As a result, school districts may employ more than one instructional program.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Lindholm-Leary and Hernandez also found that 85% of the ELLs in their study were on their way to achieving English language proficiency and cite this as an indication that the "additive bilingualism and biliteracy" (2011, p. 542) of DL programs allow students to achieve success mastering academic English. Alanís and Rodriguez (2008) analyzed Texas state assessment test (TAKS) scores, a summative measure, in their study on the academic achievement of fifth grade ELLs who received instruction in a DL program. The study centered on a well established elementary DL program using the 90/10 model.…”
Section: Comparison Of Models In Terms Of Ell Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation